History of incidence of autoimmune and oncological diseases in identical female twins - Ulcova-Gallova, Z; Brabcova, H; Kokes, V; Hradecky, L; Novotny, Z; Rokyta, Z (American journal of reproductive immunology (New York, N.Y., 2009)
PROBLEM: The aim of study was to investigate identical female twins born in 1977 suffered from autoimmune diseases (twin A - Sjogren's syndrome, and twin B - systemic lupus erythematosus). METHOD OF STUDY: It was refer retrospective analysis of both sisters suffered beside autoimmune alterations (Sjogren's syndrome and systemic lupus erythematosus) also from gynecological diseases (twin A - praecancerosis of cervix uteri, twin B - carcinoma vaginae). RESULTS: Relationships between disease activities and severities in the female twins were similar and the treatments were directed according to clinical symptoms and laboratory results. Dramatic change, unfortunately, occurred with twin B. The reason may be the association between SLE activity (lupus nephritis), hematological complication (leukopenia) and oncological vaginal recidivation. CONCLUSION: Association between autoimmune disease and gynecological cancer (or praecancerosis) is major risk than without immunology deviation. Twin A is periodically gynecologically observed.
Keywords: dospělí; Carcinoma, Squamous Cell; systémový lupus erythematodes; Female; Diseases in Twins; Vaginal Neoplasms; Twins, Monozygotic; nádory vaginy; Adult; dvojčata monozygotní; ženské pohlaví; nemoci u dvojčat; lidé; těhotenství; vedení porodu; nádory děložního čípku; Precancerous Conditions; Lupus Erythematosus, Systemic; Sjögrenův syndrom; retrospektivní studie; Delivery, Obstetric; fatální výsledek; spinocelulární karcinom; Fatal Outcome; Uterine Cervical Neoplasms; Pregnancy; Retrospective Studies; Sjogren's Syndrome; prekancerózy; Humans